Leucothoe axillaris Dog Hobble, Coastal Leucothoe: FPS-340/FP340, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the coastal leucothoe (Leucothoe axillaris), a shrub native to Florida. It describes the plant’s physical characteristics, including its height, spread, leaf arrangement, and flower and fruit features. The document also outlines the plant’s growth requirements, such as light, soil, and water needs, and its uses in landscaping. Additionally, it highlights potential pest and disease issues and offers guidance on propagation and maintenance. Coastal leucothoe is noted for its suitability in shaded, wet sites and its aesthetic appeal in various garden settings. Original publication date October 1999.